Association between peer relationships and exercise self-efficacy among college students: the mediating role of physical activity commitment - Bao, Han (Frontiers in Psychology, 2025)
PurposeThis study investigates the correlation between peer relationships and exercise self-efficacy among college students and examines the mediating role of physical activity inputs. These findings aim to enhance college students’ physical activity levels and promote their overall physical and mental wellbeing.MethodsThe Peer Relationship Scale, Exercise Self-Efficacy Scale, and Physical Activity Behavioral Intention Scale were included in a questionnaire administered to 514 university students on 12 July 2024.Results(1) There were no sex differences in peer relationships among college students (p > 0.05), but there was a sex difference in exercise self-efficacy and physical activity commitment (p < 0.05), with male students demonstrating higher levels than female students. (2) Peer relationships were positively correlated with exercise self-efficacy (r = 0.832, p < 0.05); peer relationships were positively correlated with physical activity commitment (r = 0.743, p < 0.05); and exercise self-efficacy was positively correlated with physical activity commitment (r = 0.758, p < 0.05). (3) The direct effect of college students’ peer relationships on exercise self-efficacy was significant, with an effect size of 74.26%. (4) The mediating effect of physical activity commitment between college students’ peer relationships and exercise self-efficacy was significant, with an effect size of 25.74%.Conclusion(1) There is a close relationship between college students’ peer relationships, exercise self-efficacy, and physical activity inputs. (2) Peer relationships significantly influence college students’ exercise self-efficacy, and they can also have an indirect effect on exercise self-efficacy through the pathway of action of physical activity input.